A inspeção escolar e suas implicações político-pedagógicas e ideológicas na Rede Municipal de Ensino de Uberlândia - RME/UDI: (1991-2021) - Melo, Ana Claudia de (2022)
The present study is a qualitative, retrospective, prospective, descriptive and analytical investigation, based on a bibliographic and documentary survey on the School Inspection and its political-pedagogical and ideological implications of the Municipal Education Network of Uberlândia - RME/UDI (1991 - 2021) , plus a survey carried out through a structured questionnaire (Annex A) to active and inactive inspectors, from RME/UDI (1991 – 2021), directly related to the research object. This research was developed within the scope of the State, Policy and Management (EPG) in Education line of the Graduate Program in Education (PPGED) of the Federal University of Uberlândia (UFU). The general objective of the investigation is to dialectically analyze the School Inspection and its ideological political-pedagogical implications of the Municipal Education Network of Uberlândia - RME/UDI, with a temporal cut of the period 1991 - 2021. problem that the societal transformations guided by neoliberal logic have contributed over the years to the devaluation and precariousness of the position of School Inspector of RME/UDI. In this sense, this work sought to specifically analyze the historical trajectory of school inspection in Brazil, in educational legislation and public policies, critically identifying and recognizing its different meanings/meanings and political-pedagogical and ideological implications; to critically reflect on the historical trajectory of school inspection in the legislation and public policies of the municipal education network of Uberlândia, as well as to describe and analyze in the light of the vision of servers of the School Inspection of the Municipal Public Education Network of Uberlândia, the meaning/meaning attributed to the position, as well as the limits and political-pedagogical possibilities of its praxis since the time of its creation in 1991. The historical rescue of the position of school inspector pointed to the fact that it was created during the consolidation of the capital system with the purpose of controlling, inspecting the laws and regulations established to serve the interests of the bourgeoisie in the State. The study on the inspectors' view of the creation of the sector in the RME/UDI in the 1990s points out that it emerged as a position of trust destined to control and supervise laws, regulations and processes in accordance with the vision and interests of the governments in office. . This ideological function, which began to change from the moment the sector was transformed into a career position, being partially removed, both from the investiture of its supervisory power, and from the loss of salary bonuses for those servers who started to occupy this same function. starting in 2004. From then on, the School Inspectorate began to feel the difference in the exercise of power historically attributed to positions of trust, as well as, when included by the governments in office, in the salary policies assigned to the set of education workers, characterized since the 2000s, in general terms, by the precariousness and devaluation of the profession in every sense. Regardless of the recognition of improvements in the sector resulting from the advent of computerization and the use of digital technologies, the SME/UDI School Inspection sector felt the effects of the precariousness of its world of work, starting with the accumulation of demands outside working hours, and the obligation of having to perform attributions that the sector considers not inherent to its function. The view of school inspectors also pointed to the fact that the position, in addition to distancing itself from the ideological alignment with government interests, also started not to identify general terms, with the former supervisory and control functions, seeking with this, assume functions of supervision, guidance, advice, mediation of administrative-pedagogical and political-pedagogical conflicts within the scope of RME/UDI, in line with the demands of public education as a State policy.